1985
DOI: 10.1161/01.res.57.4.618
|View full text |Cite
|
Sign up to set email alerts
|

The renal sympathetic baroreflex in the rabbit. Arterial and cardiac baroreceptor influences, resetting, and effect of anesthesia.

Abstract: Curves relating renal sympathetic nerve activity and mean arterial pressure were derived in conscious rabbits during ramp changes in mean arterial pressure, elicited by perivascular balloon inflation. The renal sympathetic nerve activity-mean arterial pressure relationship consisted of a high-gain sigmoidal region about resting, where renal sympathetic nerve activity rose or fell in response to moderate falls and rises of mean arterial pressure. With larger pressure rises, renal sympathetic nerve activity firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
153
3

Year Published

1986
1986
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(165 citation statements)
references
References 57 publications
9
153
3
Order By: Relevance
“…reflex, the baroreceptor-heart rate reflex and the renal sympathetic baroreflex (Kunze, 1981;Dorward et al 1982Dorward et al , 1985. We have now found it to occur, within 30 s, whenever there is a reversal in the direction of a slow pressure rise or fall.…”
Section: Hysteresis Shifts In Aortic Baroreceptor Unitsmentioning
confidence: 70%
See 2 more Smart Citations
“…reflex, the baroreceptor-heart rate reflex and the renal sympathetic baroreflex (Kunze, 1981;Dorward et al 1982Dorward et al , 1985. We have now found it to occur, within 30 s, whenever there is a reversal in the direction of a slow pressure rise or fall.…”
Section: Hysteresis Shifts In Aortic Baroreceptor Unitsmentioning
confidence: 70%
“…(Salgado & Krieger, 1978; Coleridge, Coleridge, Kaufman & Dangel, 1981; Dorward, Andresen, Burke, Oliver & Korner, 1982;Munch, Andresen & Brown, 1983;Coleridge, Coleridge, Poore, Roberts & Schultz, 1984;Heesch, Thames & Abboud, 1984); once established, it is stable for at least 1-2 h (Dorward et al 1982;Munch et al 1983). Receptor resetting appears to be largely responsible for the resetting of baroreflex responses, which also occurs over a similar time span (Kunze, 1981;Forward et al 1982; Dorward, Riedel, Burke, Gipps & Korner, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sterilized guide cannula (0.71-mm O.D., 22.5-mm long) was then mounted in a stereotaxic clamp, inserted into the brain, and fixed in position with dental cement. One week before the experiments, a bipolar renal nerve electrode for recording RSNA was implanted according to the method of Dorward and colleagues (11).…”
Section: Methodsmentioning
confidence: 99%
“…There is some circumstantial evidence from studies in anaesthetized animals which lend further support to this idea. It has been observed that anaesthesia augments the renin response to ACE-inhibition (Bing & Poulsen, 1975), and anaesthesia is known to depress the function of some central synapses, distorting the autonomic nervous response to various cardiovascular stimuli, in favour of sympathetic outflow (Korner et al, 1968;Zimpfer et al, 1974;Dorward et al, 1985). It would therefore seem that the renal sympathetic innervation is conveniently placed to mediate the release of renin following ACE-inhibition.…”
Section: Discussionmentioning
confidence: 99%